2004
DOI: 10.1074/jbc.m312961200
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of the Acylphosphatase from Sulfolobus solfataricus

Abstract: Protein aggregation is associated with a number of human pathologies including Alzheimer's and Creutzfeldt-Jakob diseases and the systemic amyloidoses. In this study, we used the acylphosphatase from the hyperthermophilic Archaea Sulfolobus solfataricus (Sso AcP) to investigate the mechanism of aggregation under conditions in which the protein maintains a folded structure. In the presence of 15-25% (v/v) trifluoroethanol, Sso AcP was found to form aggregates able to bind specific dyes such as thioflavine T, Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(45 citation statements)
references
References 56 publications
1
44
0
Order By: Relevance
“…Disease-associated, aggregation-prone mutants of the prion protein have pre- viously been found to display very little or no difference in thermodynamic stability compared with the wild-type protein (43,44). Furthermore, a recent report also suggests that the map of fibrillization pathways may be more complex than previously thought (45). In their system, Plakoutsi et al (45) found that aggregation and fibril formation does not necessarily involve a passage through the unfolding pathways and partially unfolded forms but rather may also occur via native or nearly native conformations.…”
Section: Kinetic Analysis Of Acid-induced Denaturation Of Ataxin-3-mentioning
confidence: 73%
See 1 more Smart Citation
“…Disease-associated, aggregation-prone mutants of the prion protein have pre- viously been found to display very little or no difference in thermodynamic stability compared with the wild-type protein (43,44). Furthermore, a recent report also suggests that the map of fibrillization pathways may be more complex than previously thought (45). In their system, Plakoutsi et al (45) found that aggregation and fibril formation does not necessarily involve a passage through the unfolding pathways and partially unfolded forms but rather may also occur via native or nearly native conformations.…”
Section: Kinetic Analysis Of Acid-induced Denaturation Of Ataxin-3-mentioning
confidence: 73%
“…Furthermore, a recent report also suggests that the map of fibrillization pathways may be more complex than previously thought (45). In their system, Plakoutsi et al (45) found that aggregation and fibril formation does not necessarily involve a passage through the unfolding pathways and partially unfolded forms but rather may also occur via native or nearly native conformations. It would seem that a similar process applies to ataxin-3, whereby conformational changes caused by the expanded polyglutamine tract do not perturb the dynamics of un/folding but are sufficient to lower the activation barrier to the fibrillization pathway and thus increase the propensity of the protein to form fibrils from a native or nearly native conformation (Fig.…”
Section: Kinetic Analysis Of Acid-induced Denaturation Of Ataxin-3-mentioning
confidence: 92%
“…Under conditions in which protofibril formation occurs more rapidly (50 mM acetate buffer, 20% (v/v) TFE, pH 5.5, 25°C), it has been shown that Sso AcP adopts initially, before aggregation starts, an essentially native fold (8,10). Two sequential phases have been detected in the aggregation process (11).…”
mentioning
confidence: 96%
“…However, by contrast with other acylphosphatases of known structure, Sso AcP contains an 11-residue, unstructured segment at the N terminus (7). In the presence of 15-25% (v/v) 2,2,2-trifluoroethanol (TFE), 50 mM acetate buffer, pH 5.5, 25°C, Sso AcP has been shown to aggregate within 30 min into structured spherical and chain-like protofibrils (8). Protofibril formation is also observed in the absence of TFE under the same conditions of pH and temperature, although the process requires weeks in this case (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation